Dynamic interactions between foreign institutional investment flows and stock market returns: The case of India - Hemantkumar P. Bulsara; Vaishali Samir Dhingra; Shailesh Gandhi (Contemporary Economics, 2015)
There has been a marked increase in the magnitude of Foreign Institutional Investments (FIIs) into India since the 1990s, resulting in increased forex reserves and liquidity and a higher-valued Indian capital market. However, such investment is more volatile than other types of flows, causing disruptive effects in the form of sudden stops (for example, the crash of the Indian stock market on January 21, 2008). This study empirically examines the dynamic relationship between FIIs and Indian stock market returns. It also analyses the effects of FIIs on Indian capital market returns, using data from January, 2004 through September, 2012. The analysis employs a Cross Correlation Function (CCF) approach, a Granger Causality Test and Vector Auto Regression after dividing the data into two parts: Pre Global financial crisis and Post Global financial crisis periods. The results of the CCF suggest bi-directional causality between FIIs and Nifty returns, whereas the Granger Causality Test and the VAR analysis suggest uni-directional causality running Nifty returns to FIIs.
Keywords: C58; F41; G10; G23; 330; Foreign Institutional Investment; Indian stock market; Cross Correlation Function approach; Granger Causality test; Vector Auto Regression